Talbot effect in the presence of interactions - Hoellmer, Philipp; Bernier, Jean-Sebastien; Kollath, Corinna; Baals, Christian; Santra, Bodhaditya; Ott, Herwig (Physical Review A, 2019)
We study both experimentally and theoretically, considering bosonic atoms in a periodic potential, the influence of interactions in a Talbot interferometer. While interactions decrease the contrast of the revivals, we find that over a wide range of interactions the Talbot signal is still proportional to the phase coherence of the matter wave field. Our results confirm that Talbot interferometry can be a useful tool to study finite-range phase correlations in an optical lattice even in the presence of interactions. The relative robustness of the Talbot signal is supported by the first demonstration of the three-dimensional Talbot effect.
CRIS-Team Scopus Importer:2023-03-27